Administrative justice in Wales: a new egalitarianism?. Issue 1 (2nd January 2017) - Nason, Sarah
Abstract: Administrative justice systems are under a variety of pressures, in particular austerity-inspired civil justice reform. I argue that such pressures do not necessitate the decline of administrative justice, and that a developing Welsh model has cross-jurisdictional appeal, especially to legal orders currently lacking a relevant organisational centre and joined-up approach. I examine the efficacy of existing conceptions of administrative justice and delineate a developing Welsh approach grounded in egalitarian principles. The nascent Welsh model emphasises reforming administrative justice hierarchies so that they work harmoniously with regulatory and value-promoting parts of the system, focusing on user perspectives and tackling the risks of less transparent forms of bureaucratic decision-making.